2016
DOI: 10.3389/fphar.2016.00347
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Therapy Modulates Telomerase Activity in Patients Free of Atherosclerotic Cardiovascular Diseases

Abstract: Background: Telomerase activity (TA) is considered as the biomarker for cardiovascular aging and cardiovascular diseases (CVDs). Recent studies suggest a link between statins and telomere biology that may be explained by anti-inflammatory actions of statins and their positive effect on TA. Until now, this effect has not been investigated in prospective randomized studies. We hypothesized that 12 months of atorvastatin therapy increased TA in peripheral blood mononuclear cells.Methods: In a randomized, placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Telomerase activity was significantly increased in isolated PBMCs in the atorvastatin group, but did not change in the placebo arm. 111 In line with these results, we have shown that pharmacologically relevant concentrations of atorvastatin increased telomerase activity by 6 fold in human and mouse PBMCs and CD4 T-lymphocytes, translating into a moderate increase in proliferation of T lymphocytes. 103 The proliferative effect of atorvastatin was ablated in the absence of the catalytic subunit TERT.…”
Section: Statinssupporting
confidence: 81%
“…Telomerase activity was significantly increased in isolated PBMCs in the atorvastatin group, but did not change in the placebo arm. 111 In line with these results, we have shown that pharmacologically relevant concentrations of atorvastatin increased telomerase activity by 6 fold in human and mouse PBMCs and CD4 T-lymphocytes, translating into a moderate increase in proliferation of T lymphocytes. 103 The proliferative effect of atorvastatin was ablated in the absence of the catalytic subunit TERT.…”
Section: Statinssupporting
confidence: 81%
“…Atualmente, estão sendo realizadas investigações para medir se estatinas podem ser utilizadas como possíveis agentes terapêuticos para a ativação da telomerase e como geroprotetores eficientes. 22 Recentemente, as células senescentes despertaram a atenção por seu potencial como alvo terapêutico para doenças relacionadas à idade, como as DCV. Estudos demonstraram que a senescência celular é equivalente à senescência epitelial, e, portanto, à senescência vascular.…”
Section: Discussionunclassified
“…Examples include not only rejuvenation biotechnologies in general, but also anti-senescence drugs (senolytics) [27,28] such as quercetin, dasatinib, navitoclax [29] , drugs or compounds such as sirtuin modulators [30] , rapamycin [31] , lifespan-extending herbs [32] , metformin [33] , telomere and telomerase modulators [34] . A common characteristic of these is that there is a clear separation between an outside agent (a physician, surgeon, healer, nutritionist) and the patient (healthy or unhealthy young or older people).…”
Section: Discussionmentioning
confidence: 99%